Derivação biliopancreática com preservação gástrica videolaparoscópica: sistematização técnica - Domene,Carlos Eduardo (2001)
BACKGROUND: The authors describe a videolaparoscopic technical variation of biliopancreatic diversion, and its rationale, as well as its preliminary results.They operated on 12 female patients, age between 26 and 49 years, BMI range 47,4 and 59,5kg/m². There were no intraoperative complications; operative time ranged from 2 to 4,5 hours; discharge in the 3rd. postoperative day. Liquid dietetic recommendations in the early period, and normal diet after the first week. One patient was readmmitted after 1 week with abdominal pain because of excessive ingestion of food; there was deep venous trombosis in one patient. Follow-up showed loss of excess weight of 27,4% after four months. Initial results of the described operation sugests it may be a good alternative to morbid obesity surgical treatment; it is strongly required a multidisciplinar pre and postoperative treatment program.